The Theory of the Trading Firm Revisited: Discussion - Grauer, Frederick L. A. (Journal of Finance, 1978)
Frederick L. A. Grauer, The Theory of the Trading Firm Revisited: Discussion, The Journal of Finance, Vol. 33, No. 3, Papers and Proceedings of the Thirty-Sixth Annual Meeting American Finance Association, New York City December 28-30, 1977 (Jun., 1978), pp. 1031-1033